A Neurocognitive Comparison of Listening to Academic Lectures and Natural Sounds: Implications for Test Validity. Issue 2 (4th May 2023) - Lee Jia Yi, Janice; Aryadoust, Vahid; Ng, Li Ying; Foo, Stacy
ABSTRACT: With the advent of new technologies, assessment research has adopted technology-based methods to investigate test validity. This study investigated the neurocognitive processes involved in an academic listening comprehension test, using a biometric technique called functional near-infrared spectroscopy (fNIRS). Sixteen right-handed university students completed two tasks: (1) a linguistic task that involved listening to a mini-lecture (i.e., Listening condition) and answering of questions (i.e., Questions condition) and (2) a non-linguistic task that involved listening to a variety of natural sounds and animal vocalizations (i.e., Sounds condition). The hemodynamic activity in three left brain regions was measured: the inferior frontal gyrus (IFG), dorsomedial prefrontal cortex (dmPFC), and posterior middle temporal gyrus (pMTG). The Listening condition induced higher activity in the IFG and pMTG than the Sounds condition. Although not statistically significant, the activity in the dmPFC was higher during the Listening condition than in the Sounds conditions. The IFG was also significantly more active during the Listening condition than in the Questions condition. Although a significant gender difference was observed in listening comprehension test scores, there was no difference in brain activity (across the IFG, dmPFC, and pMTG) between male and female participants. The implications for test validity are discussed.